Design and development of air quality management devices with sensors and web of things - Kumar Singh, Neeraj; kumar, Amardeep; Singh, Rajesh; ., Anita (International Journal of Engineering and Technology, 2018)
With the rapid increase in urbanization, there is a huge and urgent need of controlling the air quality so that we can breathe freely. We need oxygen to live and sustain life and for that controlling the environment is must otherwise it would create a great damage. According to a survey, pollution is claiming one life every 23 seconds in India and the figure can go to an extent of 1 billion people dying due to air pollution by 2030. If there would be something free on earth then it would be just Carbon. The earliest step we can take towards this cause is the detection pollutants present in the atmosphere after which the action can be taken against these pollutants. The detection can be done by the use of various sensors like MQ-2, MQ-135, DHT-11, PM10/PM2.5, AQM65 etc. and then obtaining the real-time data to the local servers by the means of IoT. The pollutants can be easily monitored when connected through the internet and local servers. The sensors will work upon a micro-controller which is used to store the data and transmission of data to the servers. Afterwards, the data can be easily accessible on the application developed.